ANALISIS FAKTOR-FAKTOR YANG MEMPENGRUHI PERINGKAT OBLIGASI PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015 - 2017 (Studi pada perusahaan non keuangan yang terdaftar di BEI 2015 -2017) - Arif Hendri Anto, 15.05.52.0156; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study examines the effect of firm size, leverage, profitability, activity, market value ratio, age of bond, guarantee, trustee reputation to bond rating. This research is conducted in Bursa Efek Indonesia by using unit of analysis of non financial company This sampling method using purposive sampling with research period of 2015 until 2017. The relationship and / or influence between variables is explained by multiple logistic regression analysis The results of this study indicate that leverage and guarantee have a significant effect, while firm size, profitability, activity, market value ratio, and age, have no significant effect on bond rating.